THE INFLUENCE OF LEADERSHIP STYLE, TRAINING AND DEVELOPMENT, AND RESOURCE AVAILABILITY ON EMPLOYEE CREATIVITY AND INNOVATION WITH JOB SATISFACTION AND CRITICAL THINKING SKILLS AS INTERVENING VARIABLES : (A CASE STUDY OF EMPLOYEES AT PT. EIGERINDO MULTI PRODUK INDUSTRI MALANG) - Witjaksono; Arief Noviarakhman Zagladi; Sopiah (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2026)
This study examines the influence of transformational leadership style, training and development, and resource availability on employee creativity and innovation, with job satisfaction and critical thinking skills as intervening variables. A quantitative approach was employed, with data collected from employees of PT. Eigerindo Multi Produk Industri Malang through structured questionnaires. Data analysis was conducted using the SmartPLS method to evaluate the relationships among variables. The results indicate that transformational leadership significantly enhances creativity and innovation by fostering a supportive work environment. Training programs focusing on the development of technical and critical thinking skills also have a strong impact on employees' ability to generate innovative solutions. Resource availability, including financial support, time, and technology, plays a crucial role in facilitating creative processes and the implementation of innovations. Job satisfaction emerges as an important mediator, strengthening the influence of leadership and training on innovation. Similarly, critical thinking skills mediate the relationship between training and creativity, empowering employees to evaluate and develop ideas effectively. This study contributes theoretically by extending transformational leadership theory, learning theory, and the resource-based view within the context of organizational innovation. Practically, it highlights the importance of organizations integrating leadership development, training programs, and resource management strategies to foster a culture of innovation.